Pharmacotherapy of inflammatory process by ginger extract (Zingiber officinale) ointment - Iryna Kravchenko; Lida Eberle; Mariia Nesterkina; Alona Kobernik (Shahrekord University of Medical Sciences, 2019)
Introduction: The anti-inflammatory activity of the ointment based on ginger extract was investigated on carrageenan-induced inflammation. Methods: Anti-inflammatory activity was investigated on the carrageenan inflammation model in rat. The animals were divided into 5 groups: first group- control (without treatment); second group- animals received preventive treatment of ointment with ginger extract two days before experiment and with subsequent treatment after administration of phlogogen; 3rd group- animals received applications of 5% ibuprofen 2 days before experiment and with subsequent treatment after induction of inflammation; fourth group - animals were treated with ginger extract ointment after one day of the phlogogen administration; fifth group - animals were treated with reference drug after one day of the phlogogen introduction. The biochemical parameters (concentration of sialic acids, seromucoids, contents of total proteins and protein fractions) of the blood of experimental animals were investigated. Results: After local application of the ointment from the ginger extract, under the conditions of its application after phlogogen inoculation, the effect was the same as anti-inflammatory effect of the ibuprofen which was used as reference drug. The preventive ointment application provided faster and more intense reduction of the inflammatory focus with returning to the background indicators on the eighth day of the experiment, and for biochemical parameters on the sixth day of therapy. Conclusion: The ointment from ginger extract shows anti-inflammatory activity by inhibiting inflammation caused by carrageenan.